Mechanosynthesis and photophysics of colour-tunable photoluminescent group 13 metal complexes with sterically demanding salen and salophen ligands. (11th October 2022) - Leon, Felix; Li, Chenfei; Reynes, Javier F.; Singh, Varun K.; Lian, Xiao; Ong, How Chee; Hum, Gavin; Sun, Handong; García, Felipe
Abstract : A series of four photoluminescent Al and In complexes were synthesised using an environmentally-benign mechanosynthesis strategy. Abstract : A series of four photoluminescent Al and In complexes were synthesised using an environmentally-benign mechanosynthesis strategy. Sterically crowded 3, 5-di- tert -butyl functionalised salophen and salen ligands and their respective complexes have been synthesised in the solid-state and fully characterised. Subsequent photophysics and electrochemistry studies of the resulting complexes suggest that these new group 13 complexes can be viable alternatives to traditional photoluminescent complexes based on expensive and low abundant noble metals. The herein-reported strategy avoids the use of organic solvents and provides a process with low environmental impact and enhanced energy efficiency.